An experimental study to characterize the effects of initial ice roughness on the wind-driven water runback over an airfoil surface. (May 2020) - Liu, Yang; Zhang, Kai; Tian, Wei; Hu, Hui
Highlights: An experimental study was conducted to examine the wind-driven water runback over an airfoil surface. An airfoil model with realistic initial ice roughness at the airfoil leading edge was manufactured. A digital image project technique was used to map water film thickness over the airfoil surface. The initial ice roughness was found to change the characteristics of the surface water runback process significantly (e.g., rivulet width, spacing, and height). Abstract: In the present study, an experimental study was conducted to characterize the effects of initial ice roughness on the transient behaviors of surface water/ice run-back over a NACA 23012 airfoil model under a glaze icing condition. The experimental study was conducted in the Icing Research Tunnel of Iowa State University (i.e., ISU-IRT). A digital image projection (DIP) technique was applied to provide non-intrusive, temporally-and-spatially-resolved measurements of the thickness distributions of the dynamic water/ice flows over the airfoil surface. Two typical surface morphologies were observed for the surface water runback over the airfoil models: water film flow and water rivulets flow. While the surface water film flow modulated with one primary wave and multiple secondary waves is observed at lower wind speed conditions (i.e., U∞  = 10 m/s), the water rivulets flow is observed at relatively higher wind speed conditions (i.e., U∞  = 15 m/s). The initial ice roughness is found to retard and shorten the primary wave formation in the water film flow. It is also found that the initial ice roughness could trap and decelerate the water flow and decrease the inertia force in the film front, which essentially delays the formation of the rivulets. The water rivulet flow trapped by the initial roughness was found to have a meandering behavior, due to which, the initially formed narrow rivulets merged into wider rivulets as they move downstream. By recognizing the film/rivulets boundary during the dynamic surface water/ice runback process, the quantitative details were extracted, i.e., the formation, transition, and development of the rivulet flows. The initial ice roughness was found to have a significant effect on the rivulet characteristics (e.g., rivulet width, spacing, and height).